ICD-11 complex Post Traumatic Stress Disorder (CPTSD) in parents with perinatal bereavement: Implications for treatment and care. (May 2021) - Martin, Caroline J. Hollins; Patterson, Jenny; Paterson, Charlotte; Welsh, Nicola; Dougall, Nadine; Karatzias, Thanos; Williams, Brian
Abstract: Introduction: The 11th revision of the WHO International Classification of Diseases (ICD-11) has identified Complex PTSD (CPTSD) as a new condition. Aim: To explore whether the new diagnosis of CPTSD (ICD11) is relevant to women who have experienced perinatal bereavement and to advance knowledge about the acceptability, feasibility and perceived impact of delivering an innovative flexible Compassionate Focused Therapy (CFT) informed treatment package to alleviate symptoms of this condition. Methods: A mixed methods study using survey and interviews was conducted. Participants first completed the International Trauma Questionnaire (ITQ) to assess if they met the criteria for PTSD or CPTSD (n=72), and subsequent semi-structured interviews (n=12) identified participants' views about different treatment approaches. Participants: A convenience sample of women who had experienced perinatal bereavement were recruited from one geographical region in Scotland. Data collection: Information was gathered about trauma experiences related to perinatal bereavement; participants' levels of PTSD or CPTSD using the ITQ; and views regarding the features of treatment options. In-depth interviews with women (n=12) and a focus group with staff (n=5) were also conducted. Findings: Of 74 participants (n=74) who fully completed the ITQ, 10.8% (n=8) met the criteria for PTSD and 29.7% (n=22) for CPTSD, equating to a total of 40.5% of participants experiencing traumatic stress. Results suggest that CPTSD is a more common condition than PTSD in people with perinatal bereavement, with qualitative data suggesting that CFT and EMDR can be useful and acceptable interventions for this population group. Conclusion: A feasibility study is recommended next to evaluate acceptability of trial processes in preparation for a definitive randomised controlled trial of a new flexible CFT informed treatment package to address PTSD and CPTSD in people with perinatal bereavement. Recommendations for practice: Routine assessment of ICD-11 CPTSD is recommended in this population group.